Instructional Insights Gained From Teaching a Research Methods Course to Chinese International Graduate Students Studying in Canada - Beres, Jacqueline L.; Woloshyn, Vera E. (Journal of International Students, 2018)
Chinese students represent an increasing proportion of the student body in Canadian postsecondary institutions (Citizenship and Immigration Canada, 2015). While studying abroad, many of these students face linguistic and sociocultural challenges (Zhang, 2016), resulting in calls for Western instructors to provide linguistically and culturally sensitive instruction (Lin & Scherz, 2014). In this qualitative study, we utilized a form of reflexive ethnography (Enfield & Stasz, 2011) to outline our experiences teaching a required research methodology course to Chinese graduate students. Specifically, we discuss our pedagogical efforts in context of utilizing students’ reported research experiences, facilitating their acquisition of subject-specific vocabulary, and fostering a collaborative learning environment. We conclude by offering instructional suggestions to others who teach research methodologies to Chinese students.